TELAAH KETELADANAN RASULULLAH SAW DALAM MENDIDIK ANAK MENURUT SYEIKH JAMAL ABDURRAHMAN - Sugeng Tri Siswoyo; Abdul Ghofur (Turats, 2023)
The purpose of this study is to find out how the example of the Prophet Muhammad in educating children in the Islamic Parenting Book by Sheikh Jamal Abdurrahman. In this study, the author uses qualitative research methods with the type of library research, namely collecting data contained in various library books that refer to the example of the Prophet Muhammad in educating children as a primary data source and then also supported by various sources. Other sources that are still relevant as secondary data sources. Then in presenting the data, the writer uses descriptive analysis method. The results of this study indicate that according to Sheikh Jamal Abdurrahman in his book entitled Islamic Parenting, the example that the Prophet Muhammad taught in educating children includes several things that parents/educators must know, namely; teaches faith/tawhid, teaches worship, teaches science, guidance and advice, and self-habituation.